Positive Politeness Strategies in Health-Related Podcast Discourse: A Pragmatic Analysis of Billie Eilish's Discussion on Tourette Syndrome - Angels Dermika PANJAITAN; Sri SUGIHARTI; Suswanto Ismadi MEGAH S (Research and Innovation in Applied Linguistics, 2026)
While previous studies have explored politeness strategies in digital communication and podcast interactions, relatively little attention has been paid to how positive politeness functions in health-related podcast discourse, particularly when discussing sensitive personal experiences. Addressing this gap, this study investigates the realization and communicative functions of positive politeness strategies in Billie Eilish's podcast interview discussing Tourette syndrome. Guided by Brown and Levinson's (1987) politeness theory, the study adopts a qualitative descriptive approach. The data were collected from a publicly available podcast interview and analyzed through the identification and contextual interpretation of utterances reflecting positive politeness strategies. The analysis identified six dominant strategies: noticing and attending to the hearer, seeking agreement, using in-group identity markers, giving reasons, expressing optimism, and minimizing potential discomfort. These strategies were employed to foster empathy, establish interpersonal solidarity, encourage openness, reduce potential face threats, and maintain conversational comfort when addressing sensitive health-related experiences. The findings demonstrate that positive politeness serves as an important interpersonal resource in facilitating supportive and empathetic communication within digital health discourse. By illustrating how politeness strategies contribute to meaningful interaction in podcast-based health communication, this study extends pragmatic research on digital discourse and offers empirical insights into the role of positive politeness in constructing rapport and promoting audience engagement in discussions of personal health experiences.